Predicting career adaptability of fresh graduates through personal factors - Anas, Ilyana; Hamzah, Siti Raba’ah (Emerald Group Holdings, 2022)
Purpose – The purpose of this paper is to determine the contribution of personal factors towards career adaptability among fresh graduates who had been employed for less than two years. This cohort is considered as entry-level employees in organisations. Several dimensions of personal factors focussed in this study were self-esteem, conscientiousness, spiritual intelligence and social support. Design/methodology/approach – This study used a quantitative approach using a cross-sectional survey. This study sample comprised fresh graduate employees (n = 423) from four Malaysian public universities. Findings – The regression model fitted the data; the personal factors significantly predicted fresh graduates’ career adaptability, F (4,418) = 31.982, p < 0.001. Conscientiousness showed the highest contribution compared to other variables, with social support being the lowest. Practical implications – Owing to challenges faced by fresh graduates as entry-level employees, continuous career adaptation in the working environment is crucial for achieving satisfaction and success in life. All stakeholders, especially in higher education institutions, play an important role in inculcating the requisite personal traits in undergraduates to enhance their career adaptability upon joining the job market. Originality/value – This study was conducted with fresh graduates as entry-level employees in Malaysia. It is hoped that the findings of this study would provide a better understanding of the impact of personal factors on career adaptability of fresh graduates in Malaysia so that the stakeholders involved could act accordingly to help fresh graduates enter the job market with the confidence to adapt to changes at the workplace.